A STUDY OF ADOLESCENTSâ ANXIETY AND ACHIEVEMENT IN ENGLISH AS A FOREIGN LANGUAGE - Fadillah, Ridha (Universitas Muhammadiyah Surakarta, 2009)
The purpose of this is to investigate whether there is relationship between studentsâ anxiety and achievement in English as a foreign language. The subjects ofthis study were second graders of among adolescents at Sekolah Menengah UmumNegeri 1 Banjarbaru, South Kalimantan. The sample was the study aged between152 sixteen and seventeen years old students at second grade. The results indicated that the studentsâ anxiety in learning English as foreign language was atmoderate level. There was no significant relationship between the score of anxietyand studentsâ achievement in English as a foreign language as a whole. But a significant negative correlation between the anxiety and studentsâ achievement wasindicated. There was difference between male and female on communication apprehension, it showed that female was more apprehensive than male in Englishcommunication but for overall anxiety, there was no difference in English language anxiety by gender at second grade in this school.Keywords: foreign language, anxiety, achievement, adolescents, gender.